2013
DOI: 10.1186/ar4409
|View full text |Cite
|
Sign up to set email alerts
|

Inducing articular cartilage phenotype in costochondral cells

Abstract: IntroductionCostochondral cells may be isolated with minimal donor site morbidity and are unaffected by pathologies of the diarthrodial joints. Identification of optimal exogenous stimuli will allow abundant and robust hyaline articular cartilage to be formed from this cell source.MethodsIn a three factor, two level full factorial design, the effects of hydrostatic pressure (HP), transforming growth factor β1 (TGF-β1), and chondroitinase ABC (C-ABC), and all resulting combinations, were assessed in third passa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Additionally, treatment of constructs with C-ABC have been reported to enhance construct tensile properties (both Young’s modulus and UTS) (Natoli et al 2009a; Natoli et al 2009b). In addition, the combination of all three stimuli has likewise generated robust neocartilage from non-articular chondrocyte sources (Murphy et al 2013). In this study, we evaluated this stimulated tissue engineered neocartilage for its ability to be sutured into a cartilage defect, giving the constructs clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, treatment of constructs with C-ABC have been reported to enhance construct tensile properties (both Young’s modulus and UTS) (Natoli et al 2009a; Natoli et al 2009b). In addition, the combination of all three stimuli has likewise generated robust neocartilage from non-articular chondrocyte sources (Murphy et al 2013). In this study, we evaluated this stimulated tissue engineered neocartilage for its ability to be sutured into a cartilage defect, giving the constructs clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulated constructs were further treated with C-ABC at 2 U/ml for 4 hours on days 15 and 29 (Murphy et al 2013; Natoli et al 2009b; Natoli et al 2009a). Control constructs were not treated with any exogenous stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…Catabolic enzyme, C-ABC, and anabolic protein, TGF-b1, were employed to enhance the mechanical properties of engineered cartilage [23]. Neocartilage was treated with 2 unit ml 21 C-ABC in CHG for 4 h on day 14.…”
mentioning
confidence: 99%
“…Expansion of fully differentiated cells in monolayer causes dedifferentiation and therefore requires a redifferentiation step and phenotypic verification before TE culture (previously described in Section 4.2). 33, 54, 59 It was previously thought that passaged cells would irreversibly lose their chondrogenic phenotype and form neocartilage with inferior functional properties. 14 Recently however, with the advent of redifferentiation protocols, it was shown that these conditions result in neocartilage with properties as good or better than neocartilage made with primary cells.…”
Section: Cells Used For Scaffold-free Tissue Engineeringmentioning
confidence: 99%
“…Using a system of expansion and redifferentiation may also allow the proliferation and phenotypic modulation of cartilaginous sources that do not suffer joint pathologies, such as costochondral, auricular, or nasal, to be used for musculoskeletal cartilage TE. 11, 59, 64 The use of expanded cells, especially those of autologous or allogeneic origin, minimizes the limitations associated with the scarcity of healthy cells, while maintaining clinical translatability of engineered cartilage.…”
Section: Cells Used For Scaffold-free Tissue Engineeringmentioning
confidence: 99%